Using Telehealth to Address Pediatric Obesity in Rural Pennsylvania. Issue 3 (3rd July 2019) - Hosseini, Hengameh; Yilmaz, Ayse
Abstract: Introduction : While for adults in Pennsylvania, obesity rates tripled from less than 10% in 1990 to 30% in 2015, the combined rates of overweight, obese, and severely obese children and adolescents in Pennsylvania are projected to approach 37.11% by the end of 2018. Method : Pediatric obesity rates in rural areas tend to be even higher than those in urban areas. Pediatric obesity needs to be addressed, since it is strongly correlated with several chronic diseases. Given the scarcity of resources to manage this trend, innovative population-based approaches are needed. Web-based telehealth, telemedicine, mobile health (mHealth), and telephone conferences have been proposed as solutions to treat and prevent childhood obesity in rural areas; the most suitable solution is through a family-based telemedicine intervention. The purpose of this study is to explore the feasibility of such a telehealth application especially for rural Pennsylvania. Results : Telehealth use in healthcare organizations in Pennsylvania is scarce; however, 92% of Pennsylvania's school districts meet the minimum internet connectivity standards. Discussions : This article, while acknowledging barriers to the adoption of the internet-based telemedicine resources, discusses solutions for increasing their availability and dissemination in rural Pennsylvania. Current internet connectivity standards in Pennsylvania schools reflect ability to participate in telehealth programs in terms of technological background, but schools are not engaged in such programs. An appraisal of the real-life challenges to implement this modality is critical and will pave the way for advocacy and implementation of useful telehealth services in low-resource areas.